2017
DOI: 10.1038/srep39918
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood circular RNA hsa_circ_0124644 can be used as a diagnostic biomarker of coronary artery disease

Abstract: The aim of the present study was to investigate the expression of circular RNAs (circRNAs) in the peripheral blood of coronary artery disease (CAD) patients and the potential use of circRNAs as diagnostic biomarkers of CAD. We first analysed peripheral blood circRNAs of 12 CAD patients and 12 control individuals by RNA microarray and found that 22 circRNAs were differentially expressed between these two groups: 12 were upregulated, and 10 were downregulated. Then, we selected 5 circRNAs as candidate biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
158
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(162 citation statements)
references
References 37 publications
3
158
0
1
Order By: Relevance
“…The expression of circRNAs in human blood and gastric fluid also increases their potential as disease biomarkers [14]. For example, Zhao et al [15]. discovered that peripheral blood hsa_circ_0124644 can be used as a diagnostic biomarker of coronary artery disease and Yin et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of circRNAs in human blood and gastric fluid also increases their potential as disease biomarkers [14]. For example, Zhao et al [15]. discovered that peripheral blood hsa_circ_0124644 can be used as a diagnostic biomarker of coronary artery disease and Yin et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches showed that circRNAs can function as potential molecular markers for disease diagnosis. For example, Cui et al showed that hsa_circRNA_103636 in peripheral blood mononuclear cells (PBMCs) can be used as a novel biomarker for the diagnosis and treatment of major depressive disorder [13], Chen et al found that hsa_circ_0000190 could be used as a new biomarker for gastric cancer [14], and Zhao et al discovered that hsa_circ_0124644 in peripheral blood can be used as a diagnostic biomarker for coronary artery disease [15]. However, there is no report regarding the use of circRNAs as biomarkers for TB.…”
Section: Introductionmentioning
confidence: 99%
“…3C). Previous study has shown that peripheral blood circular RNA is potentially used as a diagnostic biomarker for human disease [18]. We also determined whether circulating circ_0015756 expression was altered in the peripheral blood of hepatoblastoma patients.…”
Section: Resultsmentioning
confidence: 99%